Microbial control of seawater by microfiltration - Wilmer Soler T; Juan P. Soler A; Harold Durango (Universidad de Antioquia, 2010)
Recent scientific literature presents seawater as a potential aid to solve a variety of health diseases in animals and human beings because by means of its mineral and trace elements content. In Colombia, Nicaragua and Spain it is collected in a natural way from de shore and drunk; however, this can represent a health risk because of the problems related to chemical and microbiological contamination. Microbial control of seawater allows the improvement of its microbiological quality. Objective: to compare the efficiency of three microbial control methods: microfiltration, solar exposition and quarantine. Methodology: 30 samples were collected in 20-liter high density polyethylene containers in three different places in the Colombian Atlantic coast. Results: 15 samples out of 30 showed the presence of bacteria such as E. coli and halophiles bacteria like Vibrio and Aeromonas. Microfiltration through ceramic filters of 0.5 µm produces disinfection in 100% of the samples but the quarantine for five months and solar disinfection are effective in 66 and 21% respectively. The latter requires certain weather conditions to achieve disinfection and it only allows managing small quantities of water. Dicussion: Considering chemical contamination in some places which cannot be controlled through disinfection methods, the collection of water offshore in clean places is suggested and then microfiltration treatment should be performed.